Profiles of cognitive subtest impairment in the Montreal Cognitive Assessment (MoCA) in a research cohort with normal Mini-Mental State Examination (MMSE) scores. - Markwick, A; Zamboni, G; de Jager, C (2012)
The comparative ability of the Montreal Cognitive Assessment (MoCA) and MMSE to detect mild cognitive difficulties was investigated in 107 older adults. The sensitivity of the MoCA to detect cognitive impairment with a cutoff score of <26 was investigated, as compared to the MMSE across all scores, and at a cutoff of ≥27. Performance on MoCA subtests was compared at these MMSE cutoffs to determine profiles of early cognitive difficulties. The MoCA detected cognitive impairment not detected by the MMSE in a high proportion of participants, and this impairment was evident across various subtests. The MoCA appears to be a sensitive screening test for detection of early cognitive impairment.